A screening model for managing periodic pesticide application in residential lawn soils - Yuan Guo; Shenglan Xiao; Zijian Li (Environmental Advances, 2021)
To improve our understanding of the fate of pesticides after household applications and to promote lawn management practices, we have introduced a periodic modeling framework that can be simplified using a weighted approximate approach. The comparisons of the periodic model and approximate method using regular rainfall or irrigation conditions demonstrate the validity of the approximate method; based on this, the overall weighted specific loss rate and half-lives of over 3,000 organic compounds were derived. The half-lives derived from the approximate approach can be conveniently used to estimate the pesticide concentrations that remain in lawn soils. For example, over 1,500 organic compounds have estimated half-lives below 7.0 days, indicating that their concentrations will be below at least 1/16 of the initial concentrations in soils if the applications follow a monthly pattern. The model results for two common herbicides, glyphosate and 2,4-D, indicated that when following the manufacturer's suggestions, the pesticide concentration in the soil may not cause the adverse health effects modeled by the children's ingestion exposure route. For example, based on a monthly application pattern of 230 mg m−2 per event, the average concentration of glyphosate was far below the simulated safe level of 12,000 mg kg−1, even on the days immediately after the glyphosate application. However, the simulated concentrations in the lawn soils were larger than some legal limits for glyphosate in the residential soils. Although this simple model requires further validation and improvements using field data, we hope that it will help to improve future pesticide management for lawn soils.